2013
DOI: 10.1016/j.ihj.2012.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic vascular injury: Clinical profile, endovascular management and outcomes

Abstract: Prompt endovascular management is the modality of choice in comparison to NOM without AE in both pediatric and adult patients with hemodynamically compromised inaccessible intra hepatic vascular trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…[13] Mohan et al also reported successful results of prompt endovascular treatment in both pediatric and adult patients with hemodynamically compromised hepatic vascular trauma. [7] While surgical exploration has the advantage of directly visualizing an injured blood vessel, it is associated with blood loss and infection. It is also important to remember that a surgeon can only see the outside of a blood vessel and may miss significant damage to arterial intima.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13] Mohan et al also reported successful results of prompt endovascular treatment in both pediatric and adult patients with hemodynamically compromised hepatic vascular trauma. [7] While surgical exploration has the advantage of directly visualizing an injured blood vessel, it is associated with blood loss and infection. It is also important to remember that a surgeon can only see the outside of a blood vessel and may miss significant damage to arterial intima.…”
Section: Discussionmentioning
confidence: 99%
“…[5,6] Effectiveness of TCE for vascular liver injury has been well established, with success rates ranging from 85% to 100%. [6][7][8][9][10] The present study is an evaluation of the efficacy of endovascular treatment in emergency setting for patients with acute peripheral and visceral arterial injury secondary to penetrating or blunt trauma.…”
mentioning
confidence: 99%
“…For embolization of high-grade liver injuries, some previous reports have suggested that major hepatic necrosis occurs uncommonly or even does not occur. 8,21,22 However, Letoublon et al (2011) 10 proposed that proximal arterial embolization may increase the rate of liver ischaemia. In the present study, hepatic necrosis was mentioned in one patient who received proximal TAE.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanism of injury was not specified in all studies, [13][14][15][16][17][18][19][20][21][22] even if motor vehicle accident was the most frequent cause [13][14][15][16][17][18][19][20][21][22] ( Figure 1a-c). The AAST grade of liver injury was reported in almost all the studies, 13,15,17,[20][21][22] in particular in a total of 172 patients, as reported below, 18 Grade II, 53 Grade III, 77 Grade IV, 23 Grade V injuries.…”
Section: Liver Injuriesmentioning
confidence: 99%
“…Mean ISS was reported in only two studies 15,18 having an overall mean value of 20.47. Associated lesions were not specified; [13][14][15][16][17][18][19][20][21][22] authors often reported multiple associated injuries.…”
Section: Liver Injuriesmentioning
confidence: 99%